Emergence and Clonal Spread of CTX-M-65-Producing Escherichia coli From Retail Meat in Portugal - Leão, Célia; Clemente, Lurdes; Moura, Laura; Seyfarth, Anne Mette; Hansen, Inge M.; Hendriksen, Rene S.; Amaro, Ana (Frontiers in Microbiology, 2021)
The emergence and dissemination of resistance to third- and fourth-generation cephalosporins among Enterobacteriaceae from different sources impose a global public health threat. Here, we characterized by whole-genome sequencing four Escherichia coli strains harboring the blaCTX–M–65 gene identified among 49 isolates from beef and pork collected at retail. The genomic content was determined using the Center for Genomic Epidemiology web tools. Additionally, the prediction and reconstruction of plasmids were conducted, the genetic platform of the blaCTX–M–65 genes was investigated, and phylogenetic analysis was carried out using 17 other genomes with the same sequence type and harboring the blaCTX–M–65 gene. All strains harbored blaCTX–M–65, blaOXA–1, and blaTEM–1B, and one also carried the blaSHV–12 gene. Other resistance genes, namely, qnrS2, aac(6′)-Ib-c, dfrA14, sul2, tetA, and mphA, were present in all the genomes; the mcr-1.1 gene was identified in the colistin-resistant strains. They belong to sequence type 2179, phylogenetic group B1, and serotype O9:H9 and carried plasmids IncI, IncFIC(FII), and IncFIB. All strains share an identical genetic environment with IS903 and ISEcp1 flanking the blaCTX–M–65 gene. It seems likely that the blaCTX–M–65 gene is located in the chromosome in all isolates based on deep in silico analysis. Our findings showed that the strains are clonally related and belong to two sub-lineages. This study reports the emergence of CTX-M-65-producing E. coli in Portugal in food products of animal origin. The chromosomal location of the blaCTX–M–65 gene may ensure a stable spread of resistance in the absence of selective pressure.